LEGALITAS DAN IMPLEMENTASI PERJANJIAN PRA NIKAH DALAM PERLINDUNGAN HARTA PERKAWINAN MENURUT HUKUM ISLAM - Widya Firgina; Riyan Ramdani; Lena Ishelmiany Ziaharah (USRAH: Jurnal Hukum Keluarga Islam, 2026)
Prenuptial agreements are legal instruments used to regulate the status and management of marital assets, particularly amidst the increasing complexity of modern household economies. Despite having a clear normative basis, their legality and implementation still face several obstacles, including a lack of public understanding and disparate interpretations in judicial practice. This study aims to examine the legal basis, validity according to Islamic law, and the implementation of prenuptial agreements in protecting marital assets. The approach used is normative juridical research with a qualitative analysis of laws and regulations, the Compilation of Islamic Law (KHI), fiqh literature, and religious court decisions. The results show that prenuptial agreements have strong legitimacy in positive law through Article 29 of the Marriage Law and Constitutional Court Decision No. 69/PUU-XIII/2015, and are based on sharia through the principles of al-wafā’ bil ‘uqūd and maqāṣid al-syarī‘ah. Their implementation includes regulating the separation of inherited assets, mechanisms for managing joint assets, protecting family assets, and regulating financial responsibility. The challenges that arise relate to social resistance and a lack of unified interpretation among legal authorities. This research's original contribution lies in formulating a harmonized framework between the concept of agreements in Islamic law and Indonesian positive law as a basis for strengthening mechanisms for protecting marital property.